Multi dimensional segmented hydraulic fracturing impact ground pressure control and loss reduction technology for deep buried thick coal seam hard roof - Yi TAN; Yu WANG; Manchao HE; Hui LI; Wenbing GUO; Linmao LI; Weidong LIU; Shaopu ZHANG (Meitan xuebao)
Hydraulic fracturing technology is one of the effective methods for weakening the roof of coal mines and preventing rockburst. This article takes the 2305 thick coal seam fully mechanized caving working face of a coal mine in Shaanxi Province as the engineering background, and uses theoretical analysis, numerical simulation, on-site testing, and engineering monitoring methods to study the weakening control technology of the hard roof area. Based on the theory of “plastic stranded wire”, a mechanical model of the basic top “thin plate structure” is constructed, and a method is proposed to determine the hydraulic fracturing target layer by combining the accumulated bending strain energy and the distribution and response characteristics of high-energy microseismic events at the critical state of the first fracture of the hard top plate in the coal seam extraction process. According to this method, the fracturing target layer of 2305 working face is determined to be 14.50 m thick coarse sandstone; A numerical calculation model for strain softening under fluid structure coupling mode was constructed, and a comparative experiment was designed with and without directional segmented hydraulic fracturing in the target layer. The strength stress ratio parameter was introduced to analyze the local stability of the roof. The results showed that directional long drilling hydraulic fracturing effectively broke the integrity of the basic roof and shortened the step distance of the basic roof. The initial step distance was reduced by 25.81%, and the periodic step distance was reduced by 24.64%, reducing the possibility of forming huge dynamic loads and inducing impact ground pressure due to the large suspended area of the roof; Based on the geological conditions of the 2305 working face, a multi-dimensional segmented hydraulic fracturing construction plan combining directional long drilling and conventional shallow drilling was designed. During the fracturing process of directional long drilling holes No.20, No.21, and No.22, there were 30, 35, and 23 instances of pressure drop above 3 MPa, respectively. The directional segmented hydraulic fracturing caused damage to the integrity of the roof. During the conventional shallow drilling fracturing process, the expansion forms of different fractures showed different stage characteristics of two-stage stability and multi-stage development on the fracturing curve. The fracturing effect of the roof and top coal was significant; Multiple monitoring methods were used to monitor the surrounding rock activity of the 2305 working face. The implementation of multi-dimensional segmented hydraulic fracturing technology destroyed the integrity of the hard roof. Compared with the 2303 working face without hydraulic fracturing, the initial and periodic pressure step distances were reduced by 24 m and 12 m, respectively, with a reduction of 33.33% and 32.19%, effectively reducing the working resistance of the mining face support and reducing the possibility of high-energy microseismic events, providing a guarantee for underground safety production.